2021
DOI: 10.1016/j.ijwd.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and sequelae of burnout in U.S. dermatology trainees

Abstract: Background Burnout is a health care epidemic. Although burnout has been shown to affect dermatologists in multispecialty studies, there are no such studies in dermatology trainees. Objective We conducted a survey-based study of burnout in U.S. dermatology trainees to identify its drivers and sequelae. Methods All residents enrolled in a U.S. dermatology training program were eligible. The 45-question survey included the Maslach Burnout Invent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Research specifically addressing the multifaceted burnout syndrome in dermatology is accumulating. [25][26][27][28][29][30][31] While prior studies have focused on the association between physician burnout and lower patient satisfaction scores, our study suggests that PRs may function as one of numerous players that contribute to burnout and require further investigation.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Research specifically addressing the multifaceted burnout syndrome in dermatology is accumulating. [25][26][27][28][29][30][31] While prior studies have focused on the association between physician burnout and lower patient satisfaction scores, our study suggests that PRs may function as one of numerous players that contribute to burnout and require further investigation.…”
Section: Discussionmentioning
confidence: 74%
“…Approximately 80% of dermatologists in this study reported symptoms suggestive of burnout from their work, and the majority agreed to feel hardened emotionally. Research specifically addressing the multi‐faceted burnout syndrome in dermatology is accumulating 25–31 . While prior studies have focused on the association between physician burnout and lower patient satisfaction scores, our study suggests that PRs may function as one of numerous players that contribute to burnout and require further investigation.…”
Section: Discussionmentioning
confidence: 78%
“…The factors contributing to burnout are pervasive across medical specialties, encompassing burdensome bureaucratic tasks, extended working hours, insufficient acknowledgment from peers and administrators, escalating reliance on computers, and inadequate compensation 5 . In dermatology, the factors leading to burnout may differ depending on practice settings, with issues such as excessive documentation, prolonged use of electronic medical records, and a heavy patient volume being prominent concerns for dermatology residents 5,6 .…”
Section: Methodsmentioning
confidence: 99%
“…Attention to dermatologist satisfaction is important and urgent. Between 2011 and 2014, dermatology had the highest increase in burnout prevalence of all specialties [ 5 ], and 33% of dermatologists reported burnout in the 2022 Medscape National Physician Burnout and Depression survey [ 6 ]. A focus on efficiency can help improve physician satisfaction as it increases the quality, safety, and effectiveness of care while at the same time promoting positive patient interactions and work-life balance [ 4 ].…”
Section: Introductionmentioning
confidence: 99%